Influence of microbiome species in hard-to-heal wounds on disease severity and treatment duration - Chudobova, Dagmar; Cihalova, Kristyna; Guran, Roman; Dostalova, Simona; Smerkova, Kristyna; Vesely, Radek; Gumulec, Jaromir; Masarik, Michal; Heger, Zbynek; Adam, Vojtech; Kizek, Rene (The Brazilian journal of infectious diseases, 2015)
BACKGROUND: Infections, mostly those associated with colonization of wound by different pathogenic microorganisms, are one of the most serious health complications during a medical treatment. Therefore, this study is focused on the isolation, characterization, and identification of microorganisms prevalent in superficial wounds of patients (n=50) presenting with bacterial infection. METHODS: After successful cultivation, bacteria were processed and analyzed. Initially the identification of the strains was performed through matrix-assisted laser desorption/ionization time-of-flight mass spectrometry based on comparison of protein profiles (2-30kDa) with database. Subsequently, bacterial strains from infected wounds were identified by both matrix-assisted laser desorption/ionization time-of-flight mass spectrometry and sequencing of 16S rRNA gene 108. RESULTS: The most prevalent species was Staphylococcus aureus (70%), and out of those 11% turned out to be methicillin-resistant (mecA positive). Identified strains were compared with patients' diagnoses using the method of artificial neuronal network to assess the association between severity of infection and wound microbiome species composition. Artificial neuronal network was subsequently used to predict patients' prognosis (n=9) with 85% success. CONCLUSIONS: In all of 50 patients tested bacterial infections were identified. Based on the proposed artificial neuronal network we were able to predict the severity of the infection and length of the treatment.
Keywords: Superficial wounds; časové faktory; fylogeneze; Adult; senioři; Aged; Male; Sequencing; lidé; RNA, Ribosomal, 16S; lidé středního věku; RNA ribozomální 16S; Humans; neuronové sítě; stupeň závažnosti nemoci; Middle Aged; Young Adult; mikrobiota; Microbiota; Neural Networks, Computer; senioři nad 80 let; Aged, 80 and over; Time Factors; Wound Infection; mužské pohlaví; dospělí; Bacterial Typing Techniques; mladý dospělý; Phylogeny; MALDI-TOF; ženské pohlaví; techniky typizace bakterií; Severity of Illness Index; Female; Bacterial strains; infekce v ráně